2015
DOI: 10.1007/s12011-015-0236-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium, Iron and Ferritin Levels in Patients with Diabetic Retinopathy Attending Makkah Eye Complex, Khartoum, Sudan

Abstract: Diabetic retinopathy is the most common complications of diabetes mellitus that, in most occasions, lead to blindness. Multiple evidences linked the serum magnesium, iron and ferritin disturbance with diabetes and its complications. A case-control study was conducted at Makkah Eye Complex, Khartoum, Sudan, to compare the levels of serum magnesium, iron and ferritin in patients with diabetic retinopathy with diabetic patients without diabetic retinopathy (controls). Findings indicate that all patients had type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A small study performed in China found no association between magnesium deficiency and microvascular complications [ 15 ]. In other studies, hypomagnesemia was associated with diabetic retinopathy among patients with diabetes [ 17 , 18 ]. In the current study, the risk of isolated albuminuria, isolated retinopathy, and combined albuminuria and retinopathy decreased by approximately 20% for every 0.1 mmol/L increase in serum magnesium.…”
Section: Discussionmentioning
confidence: 85%
“…A small study performed in China found no association between magnesium deficiency and microvascular complications [ 15 ]. In other studies, hypomagnesemia was associated with diabetic retinopathy among patients with diabetes [ 17 , 18 ]. In the current study, the risk of isolated albuminuria, isolated retinopathy, and combined albuminuria and retinopathy decreased by approximately 20% for every 0.1 mmol/L increase in serum magnesium.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, postpartum serum magnesium level was found to be a possible predictor for type 2 diabetes mellitus development in women with GDM [26]. We have previously observed a significantly lower median level of serum magnesium in diabetic patients with diabetic retinopathy compared with diabetic without diabetic retinopathy [27].…”
Section: Discussionmentioning
confidence: 99%
“…Association of hypomagnesaemia with oxidative stress, hypoxia and poor glycemic index is an established fact already [20][21][22]. In addition, in this study we have drawn a negative ROC curve to see the minimum cut off level of serum magnesium, below which we can predict.…”
Section: Discussionmentioning
confidence: 92%